Marketingowe aspekty zarządzania muzeum - Sobocińska, Magdalena (Marketing Aspects of Museum Management, 2008)
This paper focuses on the introduction of museum functions as well as reasons and goals of using marketing in museum management. Ways of achieving those goals have also been presented in this paper. Adaptation of marketing concepts, especially the relationship marketing, for museums is related with expanding functions which museums have now to fulfill. Museums besides part of gathering and storing works of different arts, sciences and technology, and scientific elaborations of collections, set their goal to provide costumers researching the arts in an active way, by establishing a link with the masterpiece. Furthermore, museums become a place for meetings and discussions which support the exhibition activity, and sometimes even a place for fun and relaxation. Among the reasons of professionalization of museum management and applying marketing concepts in the management several things were pointed out: changes in models of financing culture, globalization and development of information technology, as well as advancement of symbolic consumption and consumption society.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 179-194